Choosing between a dichotomy of methods in stratigraphy. (21st April 2022) - Lunt, Peter; Luan, Xiwu
Abstract : An overview of stratigraphical methods here focusses on the tectonically active basins of Southeast Asia, where studies over the past three decades have tried to adopt global methods. Unfortunately, these attempts inevitably moved towards a hybrid method that is argued to be neither satisfactory or even scientific. It is proposed that, in order to understand a complex area controlled by tectonism, a paradigm shift to a fully inductive, or evidence‐based methodology is required. Initial attempts to do this are improving our understanding of the sedimentary geology, as well as enhancing plate tectonic reconstructions and mechanisms.